The New Monstrous: Digital Bodies, Genomic Arts and Aesthetics. - Nayar, Pramod K. (Nebula, 2007)
The article discusses the developments in digital technology, genome sequencing, and information and communications technology (ICT) that produce new forms of art. The author proposes that genetics is mediated through forms of visual representation, and medical imaging and genomic art show and present things that invisible to the human eye. Moreover, technology that represents the human body and the artistic forms that mediate genetic concepts are also discussed.